RECHTSZEKERHEID DALAM DAKWAAN: ANALISIS PROSEDURAL PUTUSAN NOMOR 559 K/AG/2025 BERDASARKAN ASAS HUKUM ACARA PERDATA - Desti Eka Putri Iqbal Satria; Indah Denisa Apriani; Afifa Faras Mitha; Sri Handayani (Universitas Kapuas, 2026)
This article analyzes the principle of legal certainty (Rechtszekerheid) through a procedural review of the Cilacap Religious Court Decision No. 2557/Pdt.G/2024/PA.Clp., in comparison with the Appeal Decision No. 49/Pdt.G/2025/PTA.Smg and the Cassation Decision No. 559 K/Ag/2025. The study examines key civil procedural principles, including passive judge, open trial, judicial independence, “audi et alteram partem”, efficiency, clear reasoning, and execution after 14 days. The case involves a dispute between Ritma Nungki Ekasari and Roni Dwi Arifin regarding alimony. The findings reveal inconsistencies in the application of civil procedural principles and discrepancies with SEMA RI No. 3 of 2018, particularly concerning the consideration of the husband’s economic capacity and fairness. The study concludes that judges must apply procedural principles more consistently and carefully to avoid legal defects and to ensure legal certainty from the first-instance court.